Abnormal Functional Connectivity of the Amygdala in Mild Cognitive Impairment Patients With Depression Symptoms Revealed by Resting-State fMRI - Yang, Ting; Shen, Bangli; Wu, Aiqin; Tang, Xinglu; Chen, Wei; Zhang, Zhenzhong; Chen, Bo; Guo, Zhongwei; Liu, Xiaozheng (Frontiers in Psychiatry, 2021)
Convergent evidence suggests dysfunction of amygdala functional connectivity (FC), an important part of the nervous system that deals with emotions, in individuals with depressive symptoms. At present, the pattern of amygdala functional network in mild cognitive impairment (MCI) patients with and without depression symptoms is not clear.. The current study sought to exam the features of amygdala FC in MCI patients with depression symptoms (D-MCI) using resting-state functional magnetic resonance imaging (rsfMRI). We acquired rsfMRI data in 16 MCI patients with depression symptoms, 18 non-depression MCI patients (nD-MCI), and 20 normal controls (NC) using a 3T scanner. Statistical analysis was performed to compare the strength of functional connectivity from the amygdala among the three groups. Our results suggested that D-MCI patients exhibited significant FC differences in the amygdala-mPFC network and amygdala-sensorimotor network. These results suggest that the dysfunction of the amygdala-mPFC network and amygdala-sensorimotor network might play an important role in the pathophysiological of D-MCI.